2019
DOI: 10.2147/cia.s206100
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects Of Increasing The Involvement Of Community-Dwelling Frail Older Adults In A Proactive Assessment Service: A Pragmatic Trial</p>

Abstract: BackgroundOlder adults and care professionals advocate a more integrated and proactive care approach. This can be achieved by proactive outpatient assessment services that offer comprehensive geriatric assessments to better understand the needs of older adults and deliver person-centered and preventive care. However, the effects of these services are inconsistent. Increased involvement of the older adult during the assessment service could increase the effects on older adult’s well-being.MethodsWe studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 59 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Implementation research is essential for the successful translation of evidence-based interventions into practice. Using a mixed-methods strategy, we studied the extent to which MI and goal setting were performed within the Sage-atAge+ proactive assessment program for community-dwelling older adults (65+) to identify why we failed to show the hypothesized effect on well-being ( Rietkerk, Gerritsen, et al, 2019 ). In the current study, we showed that goal setting was prevalent, but that MI fidelity and the quality of goals were suboptimal, despite high motivation by care professionals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Implementation research is essential for the successful translation of evidence-based interventions into practice. Using a mixed-methods strategy, we studied the extent to which MI and goal setting were performed within the Sage-atAge+ proactive assessment program for community-dwelling older adults (65+) to identify why we failed to show the hypothesized effect on well-being ( Rietkerk, Gerritsen, et al, 2019 ). In the current study, we showed that goal setting was prevalent, but that MI fidelity and the quality of goals were suboptimal, despite high motivation by care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…In this mixed-methods implementation study, we aimed to identify the reasons for failure to achieve improved well-being in a previous study ( Rietkerk, Gerritsen, et al, 2019 ). We found that MI fidelity and goal quality were suboptimal despite a high prevalence of goal setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most studies the application of the elicitation method was preceded by one or more training sessions for the assessors [9,31,42,46,50,51,54,56,60,64,93,94,96,112]. Different formats of training were seen across papers, including e-learnings, seminars and webinars, and workshops.…”
Section: Variation In Type and Training Of Assessorsmentioning
confidence: 99%